Analyzing physical determinants of sprint performance with the ball in semi-professional soccer - Serafin, I.; Vencúrik, T.; Petru, J.; Bokuvka, D. (Journal of Human Sport & Exercise, 2025)
Speed, strength, and the player's technical skills are among the essential attributes of soccer performance. This study aims to investigate the extent to which tests on selected physical components can predict performance in speed tests in the presence of a soccer ball. Thirty-four semi-professional soccer players participated in this study. Pearson's product-moment correlation was used to determine the relationship between variables. Linear multivariate regression was used to construct a model from the variables (3 speed and 12 strength variables) to predict the time for 10 m and 30 m sprints with the ball and the time for change of direction speed with the ball. Our selected predictors did not show a significant correlation between the 10 m sprint with the ball and the change of direction speed with the ball. The 30 m sprint with the ball was strongly correlated (r = 0.59) with the 30 m linear sprint without the ball. A regression model with independent variables was statistically significant and identified the 30 m sprint as the only predictor (F1,32 = 17.332, p < .001, Adj R2 = 0.331, SEE = 0.157), which can explain 33.1% of the variability of the data in the 30 m sprint with the ball. Our study supports the claim that the development of running speed with the ball is justified in a soccer environment. Incorporating these exercises into the training process may positively impact match performance.